2012
DOI: 10.1037/a0025953
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS-related institutional mistrust among multiethnic men who have sex with men: Effects on HIV testing and risk behaviors.

Abstract: Objective: To investigate relationships between institutional mistrust (systematic discrimination, organizational suspicion, and conspiracy beliefs), HIV risk behaviors, and HIV testing in a multi-ethnic sample of men who have sex with men (MSM), and to test whether perceived susceptibility to HIV mediates these relationships for White and ethnic minority MSM. Methods: Participants were 394 MSM residing in Central Arizona (M age = 37 years). Three dimensions of mistrust were examined including Organizational S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 47 publications
1
55
1
Order By: Relevance
“…First, none of the variables was significantly correlated with the major dependent variable, attitude towards HIV testing. These findings are contrary to the literature suggesting that cultural mistrust, medical mistrust and conspiracy theories are associated with lower odds of HIV testing [28]. There are a number of possible explanations for this lack of correlation.…”
Section: Discussioncontrasting
confidence: 56%
“…First, none of the variables was significantly correlated with the major dependent variable, attitude towards HIV testing. These findings are contrary to the literature suggesting that cultural mistrust, medical mistrust and conspiracy theories are associated with lower odds of HIV testing [28]. There are a number of possible explanations for this lack of correlation.…”
Section: Discussioncontrasting
confidence: 56%
“…Other research has demonstrated that medical mistrust and endorsement of counter-narratives are typically negatively associated with engagement in HIV treatment and prevention (e.g., HIV testing, condom use, HIV medication adherence and retention; Bogart & Bird, 2003; Bogart & Thorburn, 2005; Bogart, Wagner, Galvan, & Banks, 2010; Eaton et al, 2015; Hoyt et al, 2012). For example, endorsement of general HIV/ AIDS, government counter-narratives are associated with negative beliefs about condom use among African Americans (Bogart & Bird, 2003; Bogart & Thorburn, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] A recent study of New York MSM found that although most had seen a clinical provider recently, 39 % did not disclose sexual activity with male partners, with lower rates among African American and Latino MSM. 15 Medical mistrust, [16][17][18][19] discrimination experiences, [18][19][20][21] conspiracy beliefs, 19,22,23 and concerns about disclosure may be particularly significant barriers to PrEP access among MSM of color, as demonstrated by a recent PrEP acceptability study among African American MSM. 24 Treatment mistrust and HIV conspiracy beliefs are also linked to sexual risk-taking and nonadherence to antiretroviral treatment 22,23 ; it is unknown how mistrust may now influence PrEP use.…”
mentioning
confidence: 99%
“…34 Despite acknowledgement of medical mistrust, perceived discrimination, and disclosure difficulties among MSWs and other MSM, little research has considered differences in how MSWs experience these phenomena. Many comparative analyses of medical mistrust and disclosure among subgroups of MSM focus on differences by race and ethnicity, [15][16][17][18][19][20][21][22][23][24]35 rather than sex work. Earnshaw and colleagues have proposed a comprehensive model linking mistrust to HIV risk, 35 which suggests that intersecting stigmas (e.g., based on race, sexual orientation, sex work, or incarceration) combine to influence disparities in risk, screening, treatment, and survival.…”
mentioning
confidence: 99%